Development of a Learning Module Based on the Modified Free Inquiry Approach to Develop University Students’ Critical Thinking Skills - Sunandar Azma'ul Hadi (Universitas Muhammadiyah Sidoarjo, 2026)
Critical thinking is a key learning outcome in higher education, requiring logical, reflective, and productive reasoning for decision-making. This study aims to train and evaluate students’ critical thinking skills through the implementation of a teaching module based on a modified inquiry approach (free modified inquiry). The research employed a one-group pretest–posttest design with 37 first-semester students in the Biology Science Education program. Data were collected using a critical thinking test and analyzed quantitatively and descriptively using N-Gain indicators at both the individual level and for each skill indicator. The results show that the modified inquiry–based module effectively fosters critical thinking skills; N-Gain scores ranged from moderate to high categories, with the average improvement falling in the moderate category consistently across indicators. This improvement is associated with students’ active involvement in planning and organizing the learning process. The findings indicate that the free modified inquiry model is suitable for training critical thinking skills on the topic of membrane transport and has the potential for broader adoption to strengthen andragogical learning practices that position students as active subjects in learning.